Quality of Landrace Semen in Yolk Citrate Cement which Plus Glucose with Different Concentrations - Albertus Baku; Agustinus A Dethan; Paulus Klau Tahuk (Journal of Tropical Animal Science and Technology, 2022)
The purpose of this study was to determine the effect of using yolk citrate diluent with different concentrations of glucose added on the motility, viability, abnormalities and pH of landrace pig cement.The cement used was fresh cement from a 3 year old Landrace pig stud.This study used an experimental method using a completely randomized design (CRD) with four treatments (P1 5%, P2 10%, P3 15% and P4 20%) and four replications so that there were 16 experimental units.The results showed that the concentration of glucose in the yolk citrate diluent was not significantly different (P>0.05) on the motility of spermatozoa with the average value of each treatment being P1 (65%), P2 (60%), P3 (63, 8%) and P4 (67.5%).The percentage of spermatozoa viability was very significantly different (P<0.01) between treatments, where in treatment P2 was relatively the same as treatment P3 and P4 but higher than treatment P1 with the value of each treatment P1 (83%), P2 (90.1 %), P3 (93.5%) and P4 (91.5%). Percentage of spermatozoa abnormalities resulting from analysis of variance (ANOVA) from each treatment there was a non-significant difference (P>0.05) where the values ​​were P1 (8.2%), P2 (9.2%), P3 (8.1%) and P4 (9.2%). The pH was significantly different (P<0.05) between treatments, where P1 treatment was relatively the same as P2 but higher than P4 treatment. On the other hand, treatment P3 was relatively the same as treatment P1, P2 and P4, with the values ​​of each treatment being P1 (8.36), P2 (7.99), P3 (7.676) and P4 (6.83). It can be concluded that the use of different glucose concentrations in the egg yolk citrate diluent with good quality, namely in the P3 treatment with a glucose concentration of 15%, the average percentage of individual motility was 64%, the percentage of live spermatozoa was 93.5%, the percentage of abnormal spermatozoa was 8.1%. and the average pH of cement is 7.68. It was concluded that the quality semen of Landrace pig could be improved optimally using glucose concentration in egg yolk citrate diluent by 15%.